A Comprehensive Review of Cutaneous Manifestations Associated with COVID-19. (7th July 2020) - Rahimi, Hoda; Tehranchinia, Zohreh
Abstract : The novel coronavirus (SARS-CoV-2), the cause of coronavirus 2019 disease (COVID-19) pandemic, is associated with some cutaneous manifestations. Although the cutaneous presentations of COVID-19 are infrequent, it is of great importance for all clinicians to be aware of these manifestations, as it may contribute to sooner and better diagnosis and management of the disease, even in asymptomatic or paucisymptomatic patients. The reported cutaneous manifestations of COVID-19 are various, dispersed, and sometimes confusing. In this article, all reported cases to date were collected and classified under 6 major groups: maculopapular rash, urticaria, chilblain, vesicular lesions, livedo reticularis, and petechiae. Different characteristics of each group were discussed in detail as well.